Development and validation of a diagnostic model for the identification of chronic ocular graft-versus-host disease (oGVHD) - Shen, Zhan; Hu, Bohao; Tao, Liyuan; Ma, Jiao; Peng, Rongmei; Zhao, Yinghan; Hong, Jing (Frontiers in Medicine, 2023)
Purpose To verify the International Chronic Ocular Graft-Versus-Host Disease (ICCGVHD) Group diagnostic criteria and establish an easy-to-use and reliable diagnosis model for quick identification of chronic oGVHD. Methods This study included 180 patients (355 eyes) who underwent allogeneic hematopoietic stem cell transplantation (allo-HSCT) and visited the Peking University Third Hospital Cornea and Ocular Surface Disease Specialist Clinic from July 2020 to February 2021. The proportion of chronic oGVHD was 76.06% (279/355). Results Five complaints, including eye dryness, photophobia, foreign body sensation, eye redness, and burning sensation; six ophthalmic examinations, including Ocular Surface Disease Index (OSDI) score, corneal fluorescein staining (CFS), tear break-up time (TBUT), Schirmer’s test score without anesthesia, conjunctival score, tear meniscus height, and non-ocular GVHD-involved organs were significantly different between patients with chronic oGVHD and control group (p < 0.05). Binary logistic regression (backward LR algorithm) selection demonstrated that three variables retained diagnostic significance for chronic oGVHD: CFS (OR = 2.71 (1.92–3.81), p < 0.001), Schirmer’s test score without anesthesia (OR = 0.83 (0.76–0.91), p < 0.001), and conjunctival score (OR = 1.96 (1.13–3.42), p = 0.031). A nomogram for the identification of chronic oGVHD was developed, and its performance was examined using an internal validation cohort (118 eyes). The areas under the curve (AUCs) for the three-variable-based nomogram were 0.976 (95% CI (0.959–0.992), p < 0.01) and 0.945 (95% CI (0.904–0.986), p < 0.01) in the development and internal validation cohorts, respectively. Conclusion This concise three-variable-based nomogram based on ICCGVHD criteria could serve as an easy-to-use and reliable tool for rapid screening of chronic oGVHD.